Proceedings of the 14th International Conference on Information Processing in Sensor Networks 2015
DOI: 10.1145/2737095.2737124
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost sensor platform for large-scale wideband spectrum monitoring

Abstract: Today's radio frequency (RF) spectrum measurements are mainly performed by governmental agencies which drive around using bulky and expensive specialized hardware. This approach does not scale well, providing us with only a poor situational awareness of the actual RF spectrum usage around us. We have developed a wideband spectrum monitoring sensor for remote operation that builds upon portable and low-cost commercial off-the-shelf (COTS) hardware components with a total cost per sensor device below $100. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…6 it can be concluded that the power of the channels used for continuous broadcasts, such as TV or radio stations can be measured without any appreciable difference either by sweeping in frequency or capturing the full bandwidth at once. However, as presented in [35] channels showing a more sporadic transmission behavior make power measurements more complicated because the chance of missing a transmission is quite high when frequency sweeping. In order to get a more exact measurement of power, either a real-time spectrum analyzer or a fast sampling SDR is needed.…”
Section: ) Impact Of Signal Bandwidthmentioning
confidence: 99%
“…6 it can be concluded that the power of the channels used for continuous broadcasts, such as TV or radio stations can be measured without any appreciable difference either by sweeping in frequency or capturing the full bandwidth at once. However, as presented in [35] channels showing a more sporadic transmission behavior make power measurements more complicated because the chance of missing a transmission is quite high when frequency sweeping. In order to get a more exact measurement of power, either a real-time spectrum analyzer or a fast sampling SDR is needed.…”
Section: ) Impact Of Signal Bandwidthmentioning
confidence: 99%